Faktor-Faktor yang Berkontribusi terhadap Perilaku Politik dan Hasil Kerja Karyawan pada Perusahaan Sektor Perbankan - Bodroastuti, Tri; Tjahyono, Danie Budi (Jurnal Ilmu Ekonomi ASET, 2010)
This study aims to identify the influence of individual factors and organizationalfactors to political behavior and the work outcomes of employees in the banking sector in fivemajor cities in Java (Jakarta, Bandung, Semarang, Yogyakarta and Surabaya). The study alsoidentifies the influence of political behavior directly to the work outcomes. This study adoptsthe theory of Stephen P. Robbins that summarizes the 6 indicators of individual factors, 9indicators of organization factors, 9 indicators of political behavior, and 12 indicators of thework outcomes. Data collection was conducted by distributing questionnaires via e-mail.Respondents who had captured a number of 180, spread across five cities which are Jakarta(100 respondents), Bandung (20 respondents), Semarang (20 respondents), Yogyakarta (20respondents), and Surabaya (20 respondents). The relationship between variables in this studywere analyzed using Structural Equation Modeling (SEM). This study showed regression weightof individual factors to political behavior with regression coefficient of 0,230; organizationalfactors to political behavior with regression coefficient of 0,251; individual factors to thework outcomes with regression coefficient of 0,204; organizational factors to the work outcomeswith regression coefficient of 0,173; political behavior to the work outcomes with regressioncoefficient of 0,295. From these results known to have significant positive influence variablesof individual and organization factors to political behavior and work outcomes. Politicalbehavior is also evident in a direct and significant positive effect to work outcomes.Keywords : individual factors, organizational factors, political behavior, the workoutcomes.